2014
DOI: 10.1038/bjc.2014.419
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive surgery in combination with hyperthermic intraperitoneal chemotherapy improves survival in patients with colorectal peritoneal metastases compared with systemic chemotherapy alone

Abstract: Background:Colorectal cancer peritoneal metastasis (CPM) confers an exceptionally poor prognosis, and traditional treatment involving systemic chemotherapy (SC) is largely ineffective. Cytoreductive surgery (CRS) combined with hyperthermic intraperitoneal chemotherapy (HIPEC) is increasingly advocated for selected patients with CPM; however, opinions are divided because of the perceived lack of evidence, high morbidity, mortality, and associated costs for this approach. As there is no clear consensus, the aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
63
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 45 publications
7
63
0
6
Order By: Relevance
“…Regarding the effectiveness of CRS/HIPEC, a pooled analysis was recently performed to synthesize the results of the small number of studies that compared CRS/HIPEC with systemic chemotherapy only [36]. Regarding the effectiveness of CRS/HIPEC, a pooled analysis was recently performed to synthesize the results of the small number of studies that compared CRS/HIPEC with systemic chemotherapy only [36].…”
Section: Emerging Evidence and Topics For Further Researchmentioning
confidence: 99%
“…Regarding the effectiveness of CRS/HIPEC, a pooled analysis was recently performed to synthesize the results of the small number of studies that compared CRS/HIPEC with systemic chemotherapy only [36]. Regarding the effectiveness of CRS/HIPEC, a pooled analysis was recently performed to synthesize the results of the small number of studies that compared CRS/HIPEC with systemic chemotherapy only [36].…”
Section: Emerging Evidence and Topics For Further Researchmentioning
confidence: 99%
“…The median overall survival ranges from 32 to 62.7 months, whereas the 5-year overall survival ranges from 19 to 58 %. 4,5 Initial concerns about the morbidity and mortality of the procedure have been allayed. A systemic review of this procedure showed a mortality of 5.8 % and morbidity of 52 %, which were comparable to other major surgeries.…”
mentioning
confidence: 99%
“…The most recent meta-analysis of three case-control studies and a single randomized trial suggested that survival was significantly improved after crs, hipec, and systemic chemotherapy compared with systemic chemotherapy alone 68 . A pooled analysis demonstrated superior 2-year (odds ratio: 2.78; p = 0.001) and 5-year survival (odds ratio: 4.07; p = 0.001) with crs and hipec (n = 187) than with systemic chemotherapy alone (n = 155).…”
Section: Colorectal Cancermentioning
confidence: 99%